International crisis management : NATO, EU, OSCE and civil society: collected essays on best practices and lessons learned - Goda, Samuel; Tytarchuk, Oleksandr; Khylko, Maksym (NATO science for peace and security series. Human and societal dynamics ;, 2016)
"World affairs - especially as they pertain to Euro-Atlantic and Eurasian security - have changed significantly in recent years. The present book is an attempt to reflect on several dimensions in which these changes are impacting the field of conflict studies and international crisis management theory and practice. As it was not possible to cover all aspects of the many events that have influenced these changes, we decided to focus mainly on the situation in Ukraine, since we consider this the most important security-related milestone in recent years for the wider region. A theoretical breakdown is the first step to understanding the whole concept of the conflict management process, with its different stages, terminological discrepancies, and various explanations. An analysis of the theories dealing with conflict management and their relevance for multilateral security institutions is presented, as well as various approaches to conflict management throughout the conflict cycle. Moreover, the book focuses on the concept of conflict transformation and the importance of identity in conflicts. International organizations are one of the most important tools for dealing with crisis management, hence the roles of NATO, the EU and the OSCE are analyzed, and information provided on their activities and available tools in this field. The role of civil society, the promotion of human rights, activities related to the democratization of society, and the promotion of universally recognized values in (post- ) conflict regions in the various stages of the conflict cycle, could not be omitted. Although our focus was mainly Ukraine-related issues, readers will find here valuable information on situations in other countries as well, such as the Republic of Moldova, Afghanistan, Bosnia and Herzegovina, and Belarus. Towards the end of the book, analyses of possible future developments and new aspects of crisis management are presented, including challenges and opportunities both for the relevant international organizations and for research in this field as such. The authors of these texts are recognized authorities within their fields of expertise. Hence we are more than happy that they have shared with us their views and ideas regarding the core issue of the book - crisis management and the role of international organizations and civil society in this regard. It was an immense pleasure to read these chapters and we are sincerely grateful to each of them for contributing to this book."--Preface